Resources and sources in anthroponomastic studies: a review of contemporary references-TRAD - Fernández Juncal, María Carmen (Onomástica desde América Latina, 2022)
This paper investigates the various sources that can serve as a starting point for the study of anthroponomastic processes. We examine two types of resources for this kind of research. On the one hand, we can access more or less established repertoires, as is the case of the database provided by public institutions in different countries (censuses, registers, statistical agencies, among others), whose purpose as a public service is open and multifunctional. On the other hand, this list can be complemented by other compilations of very different origin and purpose that can be used in a subsidiary manner. These corpora are mostly compiled by the onomastics researcher himself, who uses tools such as interviews, surveys or other mechanisms from which onomastic catalogues can be established, as well as gathering other relevant information in the processes that take place to determine the impact of certain parameters in the attribution processes, specifically in that which affects personal names.